Modal Sosial Masyarakat dalam Mengatasi Limbah Minyak Jelantah melalui Program Tersenyum - Pratama, Yoga Ferdian; Sekarningrum, Bintarsih; Yunita, Desi (Department of Sociology, Faculty of Social and Political Sciences, Universitas Andalas, 2024)
Oil waste is still a problem in the community. The focus of this study is on how the Tersenyum program can overcome used cooking oil waste, with the aim of explaining the application of the used cooking oil waste management model in the Tersenyum program . The theory used is Putnam's theory of social capital, which discusses the importance of social relations and trust in society. Putnam defined social capital as the properties of social organizations, such as beliefs, norms, and networks, that can increase the efficiency of collective work. The method used is a case study with data collection techniques in the form of literature studies, observations, and interviews. This aims to obtain specific and detailed data on the social capital of the community in used cooking oil waste management through the Tersenyum program . The results of this study are social capital that has succeeded in encouraging the results of this Tersenyum program , as shown in the network aspect (Bonding Social Capital, Bridging Social Capital, and Linking Social Capital), where this Tersenyum program can be socialized and applied in the community. In the normative aspect, the success of this program is based on the establishment of applicable shared values and rules. Finally, on the aspect of trust, where the positive response of the community encourages the success of the program Tersenyum program the assimilation of the Tersenyum program as an act of charity, people have faith that this is a good program.